2008
DOI: 10.1186/1477-7819-6-139
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral gluteal metastases from a misdiagnosed intrapelvic gastrointestinal stromal tumor

Abstract: Background: The location of gastrointestinal stromal tumors (GIST) outside of the gastrointestinal system is a rare event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Histologically, EGISTs often present as spindle cells and therefore might be excluded from the differential diagnosis of spindle cell neoplasm and could be confused with the more common leiomyoma or leiomyosarcoma [11]. Some authors reported that immunohistochemistry with antibodies against CD117 and CD34 was reliable and valuable for diagnosis of EGISTs [7].…”
Section: Discussionmentioning
confidence: 97%
“…Histologically, EGISTs often present as spindle cells and therefore might be excluded from the differential diagnosis of spindle cell neoplasm and could be confused with the more common leiomyoma or leiomyosarcoma [11]. Some authors reported that immunohistochemistry with antibodies against CD117 and CD34 was reliable and valuable for diagnosis of EGISTs [7].…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, only 5 cases have been reported in English literature [1216]. Pasku et al [15] reported a case of bilateral gluteal and lung metastases in a 56-year-old female with a GIST of the pelvis, initially misdiagnosed as a uterine leiomyosarcoma. She was treated with total resection of the tumor and adjuvant imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…GISTs typically occur in patients over the age of 40 6. Approximately, 10–30% of these neoplasms are asymptomatic and are found incidentally 4.…”
Section: Discussionmentioning
confidence: 99%